Biological control of horse purslane (Trianthema portulacastrum) - Chopra, Monika; Choudhary, Madhu; Dixit, Bharti (Indian Farming, 2024)
Horse purslane also known as Trianthema portulacastrum L. (Aizoceae), hogweed, itcit, or santha, is a cultivated pantropical weed. Horse purslane is succulent, prostrate herb with ovate green leaves that has an annual life cycle and grows indeterminately. It is considered the most troublesome weed in various states of the country, infesting various important agricultural crops like maize, soybean, cotton, sugarcane, pulses etc. Though chemical herbicides are the most effective and immediate method for the majority of weeds, however, the excessive use of chemical herbicides can pollute the soil and groundwater, which can adversely affect the crops. In recent years, there has been a major emphasis on biological control of weed. When a fungus is used for the production of a biopesticide, the product is referred to as ’mycoherbicide’. Many native fungi are pathogenic to specific weed species. These fungi are used to selectively kill weeds and eliminate them from the area. Gibbago trianthemae, fungus, was identified as the causative agent of necrotic lesions on the leaves, petioles and stems of Trianthema portulacastrum L. (Horse purslane).